Transcriptional Gene Silencing (TGS) via the RNAi Machinery in HIV-1 Infections - Fatah Kashanchi; Kylene Kehn-Hall; Aarthi Narayanan; Zachary Klase; Elizabeth Jaworski; Ravi Das; Irene Guendel; Gavin C. Sampey (Biology, 2012)
Gene silencing via non-coding RNA, such as siRNA and miRNA, can occur at the transcriptional, post-transcriptional, and translational stages of expression. Transcriptional gene silencing (TGS) involving the RNAi machinery generally occurs through DNA methylation, as well as histone post-translational modifications, and corresponding remodeling of chromatin around the target gene into a heterochromatic state. The mechanism by which mammalian TGS occurs includes the recruitment of RNA-induced initiation of transcriptional gene silencing (RITS) complexes, DNA methyltransferases (DNMTs), and other chromatin remodelers. Additionally, virally infected cells encoding miRNAs have also been shown to manipulate the host cell RNAi machinery to induce TGS at the viral genome, thereby establishing latency. Furthermore, the introduction of exogenous siRNA and shRNA into infected cells that target integrated viral promoters can greatly suppress viral transcription via TGS. Here we examine the latest findings regarding mammalian TGS, specifically focusing on HIV-1 infected cells, and discuss future avenues of exploration in this field.